Reanimating horror: Gothic critique of violence and fragmentation in Shelley’s Frankenstein and Saadawi’s Frankenstein in Baghdad - Aziz, Ahmed Saad (Research Journal in Advanced Humanities, 2025)
Ahmed Saadawi wrote Frankenstein in Baghdad in 2013 in Arabic. However, it was translated in 2018. In his novel, Saadawi implemented the gothic idea about reanimation. He attempts to show how Iraq is torn apart. Further, he picturizes how sectarian violence as well as political chaos have divided Iraq. The paper argues that Saadawi’s monster acts as a powerful metaphor for the national spirit of Iraq. This symbol has clearly occurred in the novel as a hope for Iraqis. It is embodied in a composite entity stitched together from the remains of bomb victims. The paper draws a comparison to Mary Shelley’s Frankenstein (1818). It investigates how Saadawi recontextualizes the gothic tradition. He uses this tradition to critique religious extremism, which occurred after the US-invasion of Iraq in 2003. The study focuses on the monster’s role. The monster acts as an agent of vengeance. This role challenges the religious taboo against reanimation. It exposes a cycle of violence carried out by some radical religious authority. While exposing this, the paper argues that Saadawi’s narrative critically underscores the importance of coexistence and the ethics of human dignity in a post-invasion Iraq.